Use of GIS in soil fertility mapping of Rapti Municipality, Chitwan, Nepal - Oli, Biplov; Lamichhane, Sushil; Oli, Khem (Journal of Agriculture and Applied Biology, 2020)
Mapping the spatial distribution of soil fertility in a particular area gives an idea about the nutrient content in the soil which plays an im-portant role in fertilizer recommendation, sustainable soil manage-ment, integrated plant nutrient management, land use planning, and site-specific nutrient management (SSNM). A study was carried out to assess the soil fertility status of the Rapti Municipality, Chitwan, Ne-pal. A total of 120 soil samples was collected based on land use, slope, and aspects with the use of Google Earth Pro (GEP) and ArcGIS. Based on the soil test report spatial variation of soil texture, soil pH, total nitrogen, available phosphorous, and potassium of the study area was prepared. The majority of the study area (57.11%) has sandy clay soils. The soil pH was very strongly acidic to slightly alkaline with pH values ranging from 4.8 to 8.0. Soil organic matter (1.94-3.75%), total nitrogen (0.097-0.187%), available phosphorous (51.03-270.10 kg ha-1), and available potassium (169.87-358.68 kg ha-1) in the soil are within the range of medium to high in the study area. To maintain this nutrient status, the use of organic manure, reduced use of chemical fertilizers, and different soil management practices should be adopted in this area.